In Vivo Toxicity Study of Nerium oleander's Leaves and Flowers Aqueous Extracts in Mice (Cytogenetic, Biochemical and Hematological Study) (Baghdad Science Journal, 2011)
The present research was carried out to assess the toxic effect of oral administration of the aqueous extract of Nerium oleander leaves and flowers daily at doses of (25) mg/kg body weight for four weeks in mice. The toxicity of this plant parts was determined after two and four weeks by measuring the parameters of cytogenetic (mitotic index, micronucleus %), and serum levels of the hematological (RBC, Hb, WBC) and biochemical (GOT, GPT, ALT, AST) indexes in comparison with that of the control (normal saline), also clinical signs were determined. The results showed a significant decrease in mitotic index while an obvious raise was seen in micronucleus percentage in comparison with that of the control after the two periods of administration. More over significant marked changes was seen in the level of all the hematological and biochemical parameters when compared with the control. In addition to that, diarrhea with some organ lesions were also observed.